Physics of solar energy - Chen, C. Julian (John Wiley & Sons, 2011)
"This book covers the fundamental physics of the most abundant energy resource available to human society--solar energy. Similar to other technologies, the first step to achieving success is to have a firm understanding of the basic science of solar energy and its use. The subject matter of this text is designed to give the reader this solid footing, which will be the basis of research and the development of new solar engineering technologies. Homework problems and exercises to reinforce the contents along with a solutions manual for instructors. "--Provided by publisher.